Transformation by-product identification from oxidation processes of waters containing model organic micropollutants (Nonylphenol) - Toh, Jewell Zi Le (Nanyang Technological University, 2022)
Nonylphenol is a harmful compound that is foreign to living organisms and is categorized as an endocrine disrupter that could disrupt the hormonal systems of a variety of organisms. Nonylphenol accumulates in environmental matrices with high organic content, such as sewage sludge, river works, and sediments, and persists in soil and groundwater due to its physical-chemical features, such as poor solubility and high hydrophobicity, hence it should be removed through water disinfection before consumption. Halide ions like Bromide and Iodide are also increasing commonly in our water as seawater intrusion has become more severe. The transformation pathway of DBPs was investigated using both Chlorine and Chloramine disinfectants to determine which disinfectant is more effective in the removal of Nonylphenol without forming toxic DBPs. Based on my findings, Nonylphenol and 4-n-Nonylphenol were removed during the disinfection process but at the same time, many other DBPs were formed from the transformation. Due to the time constraint, the toxicology comparison of DBPs formed was not carried out and it is recommended to be done in the near future.